Determination of carbofuran and 3-hydroxycarbofuran residues in coconut water by solid-phase extraction and liquid chromatography with UV detection - Ogawa, S.; Brito, N. M.; Silva, MRS; Ribeiro, M. L.; Leite, L. A.; Dorea, H. S.; Navickiene, S.; Abakerli, R. B.; Ferreira, JMS (Taylor & Francis Inc, 2006)
A simple method was developed to determine carbofuran and 3-hydroxycarbofuran in coconut water. The procedure involved solid-phase extraction using C-18 cartridges with acetonitrile for elution. The analysis of these compounds was carried out by liquid chromatography with UV detection at 275 nm using a gradient solvent system. The method was validated with fortified samples at different concentration levels (0.01-2.5 mu g/mL). Average recoveries ranged from 81 to 95% with relative standard deviation between 1.6 and 12.5%. Each recovery analysis was repeated at least five times. Detection limits ranged from 0.008 to 0.01 mu g/mL. The analytical procedure was applied to coconut water samples from palms submitted to treatment with commercial formulation under field conditions.
Keywords: coconut water; carbofuran; 3-hydroxycarbofuran; pesticides